Work-Life-Balance - innowacyjna strategia zarządzania - Czopek, Miłosz (Work-Life-Balance : Innovative Management Strategy, 2006)
A long-term success' of an enterprise is due in large measure to the employees' satisfaction, commitment and creativity. It is the employees who have a decisive on the quality of the end product and provided services, and they also take care of the customers. Companies need to be flexible and innovative so that they can stand up to the rise in competition. Employees work the best when their duties at work are balanced by other aspects of life. Work-Life-Balance strategy makes it possible to achieve such a balance and it takes into consideration the employees' changing needs. It also allows to meet the criteria of the public responsibility of the company. Work-Life-Balance Strategy is an innovative strategy, beneficial both to the employees and the employer.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 44-50